Biomedical Co-Cr-Mo Components Produced by Direct Metal Laser Sintering1. (2016) - Girardin, E.; Barucca, G.; Mengucci, P.; Fiori, F.; Bassoli, E.; Gatto, A.; Iuliano, L.; Rutkowski, B.
Abstract: Direct Metal Laser Sintering (DMLS) is an additive manufacturing technique based on a laser power source that sinters powdered materials using a 3D CAD model. The mechanical components produced by this procedure typically show higher residual porosity and poorer mechanical properties than those obtained by traditional manufacturing techniques. In this study, samples were produced by DMLS starting from a Co-Cr-Mo powder (in the γ phase) with a composition suitable for biomedical applications. Samples were submitted to hardness measurements and structural characterization. The samples showed a hardness value remarkably higher that those commonly obtained for the same cast or wrought alloys. In fact, the HRC value measured for the samples is 47 HRC, while the usual range for CAST Co-Cr-Mo is from 25 to 35 HRC. The samples microstructure was investigated by X-ray diffraction (XRD), electron microscopy (SEM and TEM) and energy dispersive microanalysis (EDX) in order to clarify the origin of this unexpected result. The laser treatment induced a melting of the metallic Co-Cr-Mo powder, generating a phase transformation from the γ (fcc) to the ɛ (hcp) phase. The rapid cooling of the melted powder produced the formation of ɛ (hcp) nano-lamellae inside the γ (fcc) phase. The nano-lamellae formed an intricate network responsible for the measured hardness increase. The results suggest possible innovative applications of the DMLS technique to the production of mechanical parts in the medical and dental fields, where a high degree of personalization is required.